Google Sites-Based Science Learning and Higher-Order Thinking Skills in Vocational High School Students - La Ode Hanzal; Mohammad Syaifuddin; Abdulkadir Rahardjanto (International Journal of Social Sciences and Humanities, 2026)
This study examined whether Google Sites-based science learning improved higher-order thinking skills (HOTS) among tenth-grade vocational high school students. A quasi-experimental nonequivalent control group design was used with 60 students of SMK Negeri 1 Langowan, divided equally into an experimental class and a control class. The experimental class learned science through a structured Google Sites environment, while the control class received conventional instruction. Data were collected through HOTS-oriented pretest and posttest instruments, student response questionnaires, classroom observation sheets, and documentation. The findings showed a clear difference between groups. The mean posttest score of the experimental class reached 78.93, whereas the control class obtained 54.50. The experimental group also recorded a moderate N-gain of 0.59, compared with 0.18 in the control group. The independent-samples t-test indicated a significant difference (p < 0.001), confirming that the intervention contributed to higher HOTS achievement. Students also responded positively to the platform, as reflected in a questionnaire percentage of 91.08% and an activity observation score of 88.67%. Overall, Google Sites supported a more interactive, motivating, and cognitively demanding science learning process.